Proceedings of the Third Annual Deep Brain Stimulation Think Tank: A Review of Emerging Issues and Technologies - Rossi, P. Justin; Gunduz, Aysegul; Judy, Jack; Wilson, Linda; Machado, Andre; Giordano, James J.; Elias, W. Jeff; Rossi, Marvin A.; Butson, Christopher L.; Fox, Michael D.; McIntyre, Cameron C.; Pouratian, Nader; et al. (Frontiers in Neuroscience, 2016)
The proceedings of the 3rd Annual Deep Brain Stimulation Think Tank summarize the most contemporary clinical, electrophysiological, imaging, and computational work on DBS for the treatment of neurological and neuropsychiatric disease. Significant innovations of the past year are emphasized. The Think Tank's contributors represent a unique multidisciplinary ensemble of expert neurologists, neurosurgeons, neuropsychologists, psychiatrists, scientists, engineers, and members of industry. Presentations and discussions covered a broad range of topics, including policy and advocacy considerations for the future of DBS, connectomic approaches to DBS targeting, developments in electrophysiology and related strides toward responsive DBS systems, and recent developments in sensor and device technologies.